Conversores CC-CC boost-flyback de elevados ganho e rendimento - Teodoro, Stefany Huendy (2016)
This work aims to analyze solutions for processing energy from renewable sources that require DC-DC stage, high gain and efficiency. Such solutions are based on the integration of the boost converters and flyback, resulting in the topology known as boost-flyback. The main contributions of this work are a careful mathematical analysis of conventional topology and the proposal of a boost-flyback converter with zero switching commutation. The experimental confirmation of the results is performed from tests with two prototype 500W output power, 48V input voltage, 400V output voltage and 100KHz switching frequency. Maximum yield requirements of 95.4% and 96.17% are obtained for conventional solution and zero switching commutation respectively.